Образ власти в современных теориях глобализации - Бурлачук, В. (Iнститут соціології НАН України, 2009)
In history, the fates of the power and of the state are inextricably intertwined. Therefore the changes of the power's forms in modern global society have an effect on transformations of sovereignty of the modern state. As a result of globalization the monocentric structure of power of the states vying with each other is replaced by polycentric distributing of power, in which a great number of transnational and national organizations and enterprises are either competing or co-operating. Accord ing to post-modernist and neo-globalist theorists the power can not be identified with a certain center. So the power takes on an image of the network power. However it can not be hastily said, that the destruction of national state sovereignty has already happened. Globalization strikes down the identification of homogeneous, self- exclusive and self-contained area of the national state which policy rests upon the bar rack-like force of regular army, law enforcement force, state penitentiary, and monopolization of the means of legitimate violence. The economy development is out of the national state control, whereas social consequences of these processes - such as unemployment, migration, and poverty - are amassing with in the system of the national social state. The globalization results in denationalization and transformation of national state into transnational state.